Republic of Belarus : Financial Sector Assessment Program; Technical Note -Transparency of Monetary Policy and Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2006)
This technical note on Transparency of Monetary Policy on the Republic of Belarus highlights the open process for formulating and reporting of monetary policy discussions. The National Bank of the Republic of Belarus (NBRB) displays a satisfactory degree of transparency in formulation and implementation of its monetary policy. The NBRB demonstrates a good degree of transparency with regard to the reporting of monetary policy decisions. Regarding the code of conduct, officials and selected staff of the NBRB have access to privileged financial-related information that could be used for their personal financial gain.